Do gender, age, and emotional intelligence affect the emotional regulation of adolescents involved in cyberbullying? - Agustiningsih, Nia; Yusuf, Ah; Ahsan, Ahsan; Iswanti, Dwi Indah; Saifudin, I Made Moh. Yanuar (International Journal of Public Health Science (IJPHS), 2025)
The objective of this study was to explore how age, gender, and emotional intelligence impact emotion regulation in adolescents participating in cyberbullying. A cross-sectional study was conducted in January 2023, involving 108 teenagers selected through purposive sampling. Data, gathered through a demographic questionnaire, Revised Cyberbullying Inventory II, and an emotional intelligence questionnaire, were analyzed using descriptive and multiple regression methods. The findings revealed that age, gender, and emotional intelligence collectively influence situation modification, accounting for a 2.52% impact (p-value=0.024). Emotional intelligence demonstrated effects on both situation modification and attentional deployment in individuals playing the roles of victims and perpetrators (p-value=0.018). In the case of adolescents acting as perpetrators, age, gender, and emotional intelligence collectively exhibited significant influence on attention deployment, contributing to a 9.83% impact (p-value=0.01). For adolescents who abstain from participating, the modulation response is simultaneously affected by age, gender, and emotional intelligence (p-value<0.001), resulting in a 4.44% influence. Notably, age, gender, and emotional intelligence were identified as factors influencing emotion regulation at various stages, depending on whether adolescents played the roles of victims, victims-perpetrators, or perpetrators. it is recommended that mental health nurses implement tailored emotion regulation interventions for adolescents involved in cyberbullying.